Mechanical behavior of T-shaped CFST column to steel beam joint. (December 2021) - Cheng, Yu; Yang, Yuanlong; Li, Binyang; Liu, Jiepeng; Chen, Yohchia Frank
Abstract: The seismic performance of T-shaped CFST column to H-shaped steel beam joint with vertical rib stiffeners was investigated experimentally and numerically in this study. Specifically, the joint shear deformation, inter-story drift ratio, joint stiffness, and energy dissipation capacity were analyzed. The test results demonstrate that the joint with vertical stiffeners has good seismic behavior and meets the requirements of Eurocode 3 for rigid joints in a braced frame. A finite element model for the multi-cell T-shaped CFST column to H-shaped steel beam joint with vertical rib stiffeners was established to investigate the influences of the following parameters on joint strength and joint stiffness: the width-to-thickness ratio of steel tube, vertical rib dimensions, and the axial load ratio of column. The numerical results indicate that the width-to-thickness ratio of steel tube and vertical rib dimensions play an important role in improving the joint strength and stiffness. A mechanical model for the joint strength was also developed, in which the contributions from the front face and side faces of steel tube and the vertical rib stiffeners were considered. To facilitate the practical design, a simplified design method for joint strength as well as the design suggestions for detailing are proposed based on the mechanical model. Graphical abstract: Unlabelled Image Highlights: Novel joint of CFST column to H-shaped steel beam is studied experimentally. Finite element model (FEM) is developed and verified with the experimental results. Parametric study using the FEM is carried out and mechanical model for the joint strength is proposed. A simplified design method for joint strength as well as the design suggestions for detailing are proposed.